Development and Implementation of Online Learning Based on E-Learning - Deasy Yunita Siregar; Ishaq (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2025)
The development and transmission of learning today is needed to expand knowledge so that it can be easily obtained as well as online learning based on E-learning. This is useful so that interactions and learning are given to students by lecturers are easier. In the study entitled Development and implementation of online learning based on e- learning in Siyasah Departement of Faculty of Syariah dan Law UIN SU will be conducted to find out how the development of learning, strategies and supporting factors as well as inhibitors of the development of e-learning in Siyasah Departement of Faculty of Syariah dan Law UIN SU. The data collection technique is carried out by Observation, Interview, Document and Literature Study and the subject of this research are students and lecturers of Siyasah Departement of Faculty of Syariah dan Law UIN SU as much as 10% of the total number of students randomly. Consequently, only a limited number of professors have adopted e-learning within the Department of Sharia and Law at UIN SU, and overall, the implementation of an online learning-based e-learning system among lecturers is sparse. This study seeks to examine the facilitating and obstructive aspects in the advancement of e-learning.